Zimbabwean students' conceptions of selected ecological concepts - Chiromo, Alois Solomon (Routledge, 2021)
The study was aimed at identifying the conceptions held by ‘O’ Level students who were studying the Zimbabwe Integrated Science syllabus in Mutare urban high schools. The study was conducted with 409 students. The conceptions were established by administering a multiple-choice test on ecological concepts followed by face-to-face interviews with 27 respondents.